The Tooth Book - LeSieg, Theo. 1904-; McKie, Roy (New York : Beginner Books, 1981)
Rhyming text and illustrations briefly point out what animals have teeth, their uses, and how to care for them.
Keywords: Teeth -- Fiction; Stories in rhyme